MEASURE OF NON-COMPACTNESS IN THE LORENTZ SPACES - N. A. Erzakova (Научный вестник МГТУ ГА, 2016)
Geometric characteristics of regular spaces are determined. Examples of regular spaces are the Lebesgue and Lorentz spaces, in particular. For the Lorentz spaces an inequality for arbitrary subsets, connecting the measures of noncompactness and are proved. A new class of - condensing operators in the Lorentz spaces among partially-additive operators linear operators, in particular, is obtained.